Towards a Critique of Mediatisation - Jernej A. Prodnik (tripleC: Communication, Capitalism & Critique)
Mediatisation has established itself in the last decade as a key approach in media and communication studies. Its aim is to explain the vast transformations of social relations caused by the growing power of the media. I provide a theoretical and empirical critique of this approach, with a particular focus on the institutionalist (strong) approach to mediatisation. As I argue, one of the biggest problems of mediatisation is that it perceives the power of the media in a wholly abstract manner. Even though authors advocating for the mediatisation approach typically preach about holism, their works often narrowly focus on the media, without embedding them in the social totality. This leads to a flawed approach, primarily due to the excessive media-centrism. For a critique of the ontological, epistemological and theoretical failures of mediatisation, I largely base the article on two critical approaches to the media and communication research: critical sociology of the media and political economy of communication. Empirically and mostly for illustrative purposes, the article is based on semi-structured interviews with representatives of Slovenian political parties. Three fundamental issues are identified based on this focus of the paper: mediatisation fails to distinguish between the form and content of communication; it does not make a proper distinction between public political communication and political activity; and it ignores the non-public parts of politics and deep inequalities, which influence the political process. Mediatisation generally bypasses these issues, in turn also ignoring the wider relations of power in capitalist society and how they change.